Information literacy search skills among post-graduate students at the federal University of Agriculture, Abeokuta, Nigeria (2018)
This study assessed the information literacy skills possessed by post- graduate students of the Federal University of Agriculture, Abeokuta (FUNAAB), and the extent to which they used these information literacy skills in their academic works. Descriptive survey approach was adopted for this study. A structured questionnaire that discussed the information needs, information sources, the level of information literacy skills and benefits of instructional programme was the instrument for data collection and was randomly administered on the postgraduate students of nine colleges during the last semester of 2016/17 academic year. 150 copies of questionnaire were distributed and 135 were returned giving a response rate of 90%. The data collected were analyzed using simple percentages and means. The study revealed that most of the students were aware of the information sources which were available in the library. The students mostly relied on the internet/search engines, textbooks, periodical/ journals, professionals and colleagues for information. They rarely used electronic resources such as AGORA, TEEAL and HINARI. This could be due to a lack of awareness and skills necessary to search databases. Some suggestions were made by the respondents according to their need to improve their information literacy skill such as access to online sources, organizing instructional programmes at the faculty libraries, creating more awareness on instructional programmes, avoiding copyright issues in research and how to use academic databases. The study recommends a great deal of communication and collaboration among librarians and faculty members. They need to work closely to integrate information literacy skills with existing curricular goals.